EMPIRICAL STUDY OF THE EFFECT OF INVESTMENT STRUCTURE ON THE PROFITABILITY OF LISTED COMPANIES IN TEHRAN STOCK EXCHANGE - Mandi Salehi; Hashem Valipour; Sharham Shanei (Indonesian Management and Accounting Research, 2010)
The purpose of this research is the survey of effect of investment structure on the profitability of listed companies in Tehran Stock Exchange (TSE). To do it, selected 100 companies of 13 different industries as the statistical sample and by fitting multivariable regression models with table data, have been surveyed for the relationship between investment structure scales and company's profitability during 6-years period (2002-2007) for sample companies.The results of the research show that there is a positive relationship between short-term debt to assets and company's profitability and also between total debts to total assets and profitability. But there is a negative relationship between long-term debt to assets and profitability.Keywords: Investment structure, Profitability, Tableau data